Assessment of sediment and organic carbon exports into the Arctic ocean: The case of the Yenisei River basin. (1st July 2019) - Fabre, C.; Sauvage, S.; Tananaev, N.; Noël, G. Espitalier; Teisserenc, R.; Probst, J.L.; Pérez, J.M. Sánchez
Abstract: The export of organic carbon export by the rivers to the oceans either as particulate organic carbon (POC) or dissolved organic carbon (DOC) is very sensitive to climate change especially in permafrost affected catchments where soils are very rich in organic carbon. With global warming, organic carbon export in both forms is expected to increase in Arctic regions. It should affect contemporary biogeochemical cycles in rivers and oceans and therefore modify the whole food web. This study tries to understand complex processes involved in sediment, POC and DOC riverine transport in the Yenisei River basin and to quantify their respective fluxes at the river outlet. The SWAT (Soil and Water Assessment Tool) hydrological model is used in this study to simulate water and suspended sediment transfers in the largest Arctic river. POC and DOC export have been quantified with empirical models, adapted from literature for the study case. First, the hydrological model has been calibrated and validated at a daily time step for the 2003–2008 and the 2009–2016 periods respectively, and its output has been compared with field data for water and sediment fluxes. Based on conceptualization of transfer processes, calibration on climate and soil properties has been performed in order to correctly represent hydrology and sediment transfer in permafrost basins. Second, calibration of empirical models for DOC/POC transport have been performed by comparing their output with field data, available from 2003 to 2016. Our study reveals that SWAT is capable of correctly representing hydrology, sediment transfer, POC and DOC fluxes and their spatial distribution at a daily timescale, and outlines the links between these fluxes and permafrost features. Our simulation effort results in specific sediment, POC and DOC fluxes of 2.97 t km −2 yr −1, 0.13 t km −2 yr −1 and 1.14 t km −2 yr −1 for the period 2003–2016 which are in the range of previous estimates. About 60% of the total fluxes of sediment, DOC and POC to the Arctic Ocean are exported during the two months of the freshet. Spatial analysis show that permafrost-free areas have returned higher daily organic carbon export than permafrost affected zones, highlighting the thawing permafrost effect on carbon cycle in climate change feedback. Highlights: Our study reveals new probes in modeling daily sediment and organic carbon exports. Around 60% of sediment and organic carbon loads are exported during the freshet. Permafrost free areas are the most contributive to daily organic carbon exports.